2019
DOI: 10.1111/jdv.15951
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome alterations in allergic and inflammatory skin diseases – an update

Abstract: The human microbiome is a wide range of microorganisms residing in and on our body. The homeostasis between host immune system and the microbial environment allows mutual benefits and protection. Physiological bacterial colonization is essential for the establishment of organism immunity. The human microbiota ecosystem can be divided into several compartments, out of which intestinal flora strongly affects our health and plays a crucial role in the pathophysiology of many diseases. The gastrointestinal tract, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 124 publications
(282 reference statements)
2
92
0
3
Order By: Relevance
“…The gut microbiome may contribute directly to alterations in the skin microbiome and the skin may be altering the gut microbiome—a newly emerging bidirectional signaling concept that has been labeled the “skin‐gut‐axis.” Alterations in the gut microbiome are directly correlated to clinically relevant changes in the manifestations of skin diseases such as psoriasis, atopic dermatitis, and acne . Although similar correlations have not yet been published for microbiomes of the gut and chronic skin wounds, several studies suggest that one may strongly influence the other.…”
Section: Parallel Mechanisms Between Gut‐brain‐axis and Skin‐brain Axismentioning
confidence: 99%
“…The gut microbiome may contribute directly to alterations in the skin microbiome and the skin may be altering the gut microbiome—a newly emerging bidirectional signaling concept that has been labeled the “skin‐gut‐axis.” Alterations in the gut microbiome are directly correlated to clinically relevant changes in the manifestations of skin diseases such as psoriasis, atopic dermatitis, and acne . Although similar correlations have not yet been published for microbiomes of the gut and chronic skin wounds, several studies suggest that one may strongly influence the other.…”
Section: Parallel Mechanisms Between Gut‐brain‐axis and Skin‐brain Axismentioning
confidence: 99%
“…An imbalanced gut microbiome, a pathological state named intestinal dysbiosis, has a negative impact on skin function and integrity [35,36]. O'Neill et al found that the gut microbiome can influence skin homeostasis via regulating the coordinate epidermal differentiation and immune system, although the mechanism is not yet fully elucidated [33].…”
Section: Gut Microbial and Skin-gut Axis In Psoriasismentioning
confidence: 99%
“…[5][6][7] In consequence, the role of the skin microbiome has become one of the major current frontiers of dermatological research. [8][9][10][11] However, compared with the extensively researched skin surface microbiome, [12][13][14][15][16] the specific microbiome of human hair follicles (HFs) has been relatively under-investigated, beyond pathogen-induced bacterial or fungal folliculitis, 17 hidradenitis suppurativa (HS), [18][19][20][21] folliculitis decalvans 22 and acne vulgaris. [23][24][25][26][27][28] Yet, a microbiome-centred perspective on translational human hair research is becoming ever more important, as hair growth disorders that had not previously been viewed from this perspective, such as alopecia areata (AA) 29,30 and androgenic alopecia, 31 have come under microbiological scrutiny.…”
mentioning
confidence: 99%